Examining the Contemporary Worker and the Workplace From a Leadership-as-Practice Perspective: A HRD Opportunity - Joseph A. Raelin (Human Resource Development Review, 2024)
In this article the author uses the lens of leadership-as-practice (L-A-P) to analyze the concerns of the worker in the contemporary workplace and proposes both new insights and potential remediations through a post-humanistic leadership centered on practice. L-A-P is designed to probe underneath the accepted or “natural” human resource practices to uncover the power dynamics in the workplace that have led to challenges to the worker in the form of burnout, lack of autonomy, and detachment. After introducing the practice approach to the workplace, the paper interrogates the potential value of leadership being viewed as a collaborative agency constituting changes in the trajectory of prefigured work practices that can have affirmative consequences via its ethical and critical approach to human resource development.
Keywords: I21; J24; M10; M12; M14; M53; M54; 330; Workers and the Workplace; Leadership-as-Practice; Organizational Change; Collaborative Agency; Reflexivity; Critical Management Studiese